Abnormalities in Tooth Formation after Early Bisphosphonate Treatment in Children with Osteogenesis Imperfecta - Malmgren, Barbro; Thesleff, Irma; Dahllöf, Göran; Åström, Eva; Tsilingaridis, Georgios (Calcified tissue international, 2021)
Treatment with intravenous bisphosphonate (BP) in children and adolescents with osteogenesis imperfecta (OI) started in Sweden in 1991. No human studies on the role of BP therapy in development of disturbances in tooth mineralization or tooth morphology have been published. The study cohort comprised 219 individuals who were divided into four groups: group 1, BP treatment onset before 2 years of age ( n = 22); group 2, BP treatment onset between 2 and 6 years of age ( n = 20); group 3, BP treatment onset between 6 and 10 years of age ( n = 13); and a control group of patients with OI who had not received BP therapy ( n = 164). The chi-square test was used in between-group comparisons of the prevalence of tooth agenesis. The prevalence of tooth agenesis was significantly higher in children who began BP treatment before the age of 2 years (group 1; 59%,) compared to the controls (10%; p < 0.001) and to children who had begun BP therapy between ages 2 and 6 years (group 2; 10%; p = 0.009) or between ages 6 and 10 years (group 3; 8%; p = 0.003). Different types of disturbances in the enamel formation were seen in 52 premolars, where 51 were seen in those who began BP treatment before the age of 2 years. To conclude, starting BP treatment before the age of 2 years increases the risk of abnormalities in tooth formation manifesting as morphological aberrations, tooth agenesis, and enamel defects.